Spatial Cluster Analysis and Key Influencing Factors of African Swine Fever in China (2018-2021) - Wang, Liyuan; Hassan, Latiffah; Toung, Ooi Peck; Li, Xia (Korean Society of Veterinary Science, 2025)
Importance: African swine fever (ASF) is a significant transboundary disease with profound global economic impacts. ASF, caused by the Asfarviridae virus, is highly resilient and has caused substantial economic losses in affected regions, with no available vaccination or treatment. We conducted a comprehensive analysis of the spatial clusters and potential factors contributing to the ASF epidemic in China from August 2018 to April 2021. Objective: The study aimed to trace ASF transmission, map the spatial distribution and spread dynamics, and model the spread to evaluate the potential control strategies. Methods: Standardized deviational ellipse analysis was used to identify the directionality and distribution of ASF outbreaks. Ordinary least squares regression and geographically weighted regression were applied to account for spatial heterogeneity and explore the localized relationships within the data set. Results: The ASF transmission in China was delineated across three phases, characterized by an initial rapid spread, a subsequent westward expansion, and a final plateau phase with a southwestward trend. The key factors influencing ASF transmission included the pig population density, wind speeds, altitude, and the presence of high-risk roads, with seasonality also playing a significant role in the disease incidence. Conclusions and Relevance: This research highlights the significant impact of small-scale farming practices and the live pig transportation network on ASF spread. In addition, it identifies key epidemiological factors, including the pig density and seasonal variations, which are crucial for developing effective disease control strategies.